Awal Perang Dunia II di Koran Bintang Borneo - Putra, Zidan Aji Pangestu (Langgong: Jurnal Ilmu Sosial dan Humaniora, 2022)
This research aims to (1) find out the background of World War II, (2) find out Political News in the Bintang Borneo in September 1939, (3) Learning about the German invasion of Poland. This research uses a historical method which consists of five stages, namely: 1) Topic selection, namely the stage for choosing the topic to be researched. 2) Heuristics, namely stages to search for and collect sources relevant to the topic being studied. 3) Source criticism (Verification), namely the stage of whether the sources that have been collected are acceptable believed to be true 4) Interpretation, namely the stage of constructing a framework for mass events past from the facts that have been gathered. 5) Historiography, namely the stage of writing the results research that has been carried out based on data that has been collected into a work history. From the research results it can be concluded that on September 1 1939, Germany attacked Poland. Britain and France responded by declaring war on Germany, marking the start of World War II. Followed by the Soviet Union which attacked from the east on 17 September 1939 as a result of the Molotov-Ribbentrop non-aggression agreement in Moscow on 24 August 1939 which agreed that Poland would be divided for them. With two superpowers invading its territory, the Polish army disintegrated and the Polish government evacuated to Romania. In the end, Poland was divided between Germany and the Soviet Union.